Lacunas enfrentadas por profissionais e familiares na assistência ao doente fora de possibilidade de cura - Nascimento, Marcieli Borba; Fagundes Santana, Lucas; da Cunha Paris, Matheus; Francisco de Oliveira Gabriel, Katiuscia; Almeida Santos, Vanderleia (Revista de Saúde, 2023)
With the increase in life expectancy, there is consequently an increase in non-communicable chronic diseases. Thus putting cancer records high. Today, cancers are one of the biggest public health problems. Thus, the objective of this work was to elucidate how and which impositions faced by health professionals and family members / caregivers of patients framed in paliative health, through a narrative review of the literature. A search was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), National Library of Medicine of the USA (PUBMED) and ScienceDirect databases, with the assistance of the Mendeley reference manager. The articles were covered between the years 2016 - 2021. As a research strategy developed to identify the articles included and selected for this study, it was based on the descriptors contained in the list of Descriptors in Health Science (DeCS) and their applications in the Portuguese language: [(Oncology) AND (Quality of death)]. Regarding the results, they were scored in two themes of higher quality. a) the health professional's view of terminal oncology care; b) Family members and caregivers as protagonists of end-of-life care. Finally, it was concluded that the biggest gaps were: difficult decision making, frustration when dealing with the loss of the individual. It is also mentioned the importance of academic training aimed at preparing future professionals in relation to palliative care and that much can be done to alleviate their suffering.